MATH 4510/5510: Brown Congruence-1 Notes on Congruence1 Axiom 1 (C-1). If A and B are distinct points and if A′ is any point, then for each ray r emanating from A′ there is a unique point B ′ on r such that AB ∼ = A′ B ′ . Axiom 2 (C-2). If AB ∼ = EF . Moreover, every segment is congruent to = EF , then CD ∼ = CD and AB ∼ itself. Axiom 3 (C-3: Segment Addition). If A∗B ∗C, A′ ∗B ′ ∗C ′ , AB ∼ = A′ B ′ , and BC ∼ = B ′ C ′ , then AC ∼ = A′ C ′ . −−−→ Axiom 4 (C-4). Given any ∠BAC, and given and ray A′ B ′ emanating from a point A′ , then there is a −−→ ←−→ unique ray A′ C ′ on a given side of line A′ B ′ such that ∠B ′ A′ C ′ ∼ = ∠BAC. Axiom 5 (C-5). If ∠A ∼ = ∠C. Moreover, every angle is congruent to itself. = ∠C, then ∠B ∼ = ∠B and ∠A ∼ Axiom 6 (C-6: SAS). If two sides and the included angle of one triangle are congruent to two sides and the included angle of another triangle, then the two triangles are congruent. Corollary 1 (Corollary to SAS). Given △ABC and segment DE ∼ = AB, there is a unique point F on a ←→ given side of DE such that △ABC ∼ = △DEF . −−→ ←→ Proof. By C-4 there is a unique ray DG on the given side of DE such that ∠BAC ∼ = ∠EDG. By C-1, there −−→ is a unique point F on DG such that AC ∼ = DF . By SAS, △ABC ∼ = △DEF . Proposition 10. If in △ABC we have AB ∼ = AC, then ∠B ∼ = ∠C. Proof. Consider the correspondence of vertices A ↔ A, B ↔ C, C ↔ B. By hypothesis AB ∼ = AC, and by C-5 ∠A ∼ = ∠C. = △ACB. By the definition of congruent triangles ∠B ∼ = ∠A. Then by SAS △ABC ∼ Proposition 11 (Segment Subtraction). If A∗B ∗C, D ∗E ∗F , AB ∼ = DE, and AC ∼ = DF , then BC ∼ = EF . −−→ Proof. Suppose BC 6∼ = EG. By the RAA = EF (RAA). By C-1, there is a point G on EF such that BC ∼ ∼ ∼ hypothesis F 6= G. Since AB ∼ DE by hypothesis, and BC EG we have AC = = = DG by C-3. By ∼ hypothesis, AC ∼ DF , so by C-2, DG DF . By the uniqueness in C-1 G = F . This is a contradiction, so = = BC ∼ EF . = Proposition 12. Given AC ∼ = DF , then for any point B between A and C, there is a unique point E between D and F such that AB ∼ = DE. −−→ Proof. By C-1 there is a unique point E on DF such that AB ∼ = DE. Suppose E is not between D and F (RAA). By the definition of ray, either E = F or D ∗ F ∗ E. Suppose E = F . B and C are distinct points −−→ on AB by B − 1, but DE ∼ = AB and DE ∼ = AC. This contradicts C-1, so E 6= F . Now suppose D ∗ F ∗ E. −→ By C-1 there is a unique point G on the ray opposite to CA such that CG ∼ = F E. By C-3, AG ∼ = DE. This contradicts the uniqueness part of C-1, since AB ∼ = DE. Hence E is between D and F . Definition. AB < CD (or CD > AB) means that there exists a point E between C and D such that AB ∼ = CE. Proposition 13 (Segment Ordering). 1. Exactly one of the following conditions holds (trichotomy): AB < CD, AB ∼ = CD, or AB > CD. 2. If AB < CD and CD ∼ = EF , then AB < EF . 3. If AB > CD and CD ∼ = EF , then AB > EF . 4. If AB < CD and CD < EF , then AB < EF (transitivity). Proof. 1 The statements of the propositions and many proofs are taken from the book Euclidean and Non-Euclidean Geometries by M. Greenberg. MATH 4510/5510: Brown Congruence-2 −−→ 1. Suppose AB and CD are not congruent. By C-1, there exists a point E on CD such that AB ∼ = CE. By definition of ray, either C ∗ D ∗ E or C ∗ E ∗ D. If C ∗ E ∗ D, then AB < CD by definition of <. −−→ Suppose C ∗ D ∗ E. By Proposition 3.12, there is a unique point F on AB between A and B such that CD ∼ = AF . Then AB > CD by definition of <. 2. Since AB < CD, there is a point P between C and D such that AB ∼ = CP . Since CD ∼ = EF , by Proposition 3.12, there is a unique point Q between E and F such that CP ∼ = EQ. By C-2, AB ∼ = EQ, so AB < EF . 3. Since AB > CD, there is a point P between A and B such that AP ∼ = EF . Then = CD. Suppose CD ∼ by C-2, AP ∼ = EF , so AB > EF . ∼ CP . Since CD < EF , there is 4. Since AB < CD, there is a point P between C and D such that AB = a point Q between E and F such that CD ∼ = EQ. By Proposition 3, there is a point R between E and Q such that CP ∼ = ER. By C-2, AB ∼ = ER. Since E ∗ R ∗ Q and E ∗ Q ∗ F , we know by Proposition 3.3 that E ∗ R ∗ F . Hence, AB < EF . Proposition 14. Supplements of congruent angles are congruent. −−→ −−→ −−→ Proof. Suppose ∠ABC ∼ = ∠DEF . Let BP be the ray opposite to BA and let EQ be the ray opposite to −−→ ∼ ∠F EQ. ED. We want to show ∠CBP = C P F B A E Q D Since the points A, C, and P are given arbitrarily on the sides of ∠ABC and ∠CBP , by C-1 we can choose the points D, F , and Q on ∠DEF and ∠F EQ such that AB ∼ = DE, CB ∼ = F E, and BP ∼ = EQ. ∼ ∼ Then △ABC = △DEF by SAS. By the definition of congruent triangles, AC = DF , and ∠A ∼ = ∠D. By C-3, AP ∼ = DQ. Then again by SAS, △ACP ∼ = △DF Q. By the definition of congruent triangles CP ∼ = FQ ∼ ∼ and ∠P = ∠Q. And again by SAS, △CP B = △F QE, so ∠CBP ∼ = ∠F EQ. Proposition 15. 1. Vertical angles are congruent to each other. 2. An angle congruent to a right angle is a right angle. Proof. −−→ −−→ 1. By definition two angles are vertical if they allow labeling ∠ABC and ∠DBE where BA and BD are −−→ −−→ opposite, and BC and BE are opposite. A E B D C MATH 4510/5510: Brown Congruence-3 ∠ABC is the supplement to ∠ABE and ∠DBE is the supplement to ∠ABE. By C-5 ∠ABE ∼ = ∠ABE, so by Proposition 5 ∠ABC ∼ = ∠DBE. −→ ∼ ∠ABC. Suppose P is a point on the ray opposite to − 2. Suppose ∠ABC is a right angle and ∠DEF = BC −−→ and Q is a point on the ray opposite EF . We need to show ∠DEF ∼ = ∠DEQ. Since ∠ABC ∼ = ∠DEF , ∼ by Proposition 5, their supplements are congruent, i.e. ∠ABP = ∠DEQ. By the definition of right angle ∠ABC ∼ = ∠DEQ. = ∠DEQ. Again by C-5 ∠DEF ∼ = ∠ABP , so by C-5 ∠ABC ∼ Proposition 16. For every line l and every point P there exists a line through P perpendicular to l. Proof. Either P lies on l or it does not. Assume first that P does not lie on l, and let A and B be any −−→ −−→ two points on l by I-2. By C-4 there is a ray AX such that AX is on the opposite side of l as P and −−→ ∠XAB ∼ = ∠P AB. By C-1 there is a point P ′ on AX such that AP ∼ = AP ′ . Since P and P ′ are on opposite ′ ′ sides of l, P P intersects l at a point Q between P and P . If Q = A, ∠P AB and ∠P ′ AB are supplementary. Since these angles are congruent, they are right angles, so P P ′ ⊥ l. If Q 6= A, then AQ ∼ = AQ by C-1, so △P AQ ∼ = ∠P ′ QA. Hence P P ′ ⊥ l. = △P ′ AQ by SAS. By the definition of congruent triangles ∠P QA ∼ Now suppose P lies on l. By Proposition 2.3 there is a point not on l. By the above argument we can construct a line perpendicular to l through this point, thereby obtaining a right angle. By C-4, there is a unique ray on a particular side of l emanating from P such that ∠P with one side contained in l is congruent to a right angle. By Proposition 3.15, ∠P is a right angle. The side of this angle not contained in l is contained in a line perpendicular to l through P . Proposition 17 (ASA). Given △ABC and △DEF with ∠A ∼ = ∠D, ∠C ∼ = ∠F , and AC ∼ = DF . Then ∼ △ABC = △DEF . Proof. By C-1, there is a unique point X on DE such that AB ∼ = DX. By hypothesis ∠A ∼ = ∠D and ∼ ∼ AC = DF , so △ABC = △DXF by SAS. By the definition of congruent triangles ∠C ∼ = ∠DF X. By −−→ −−→ hypothesis ∠C ∼ = ∠DF E, so by the uniqueness of C-4 F E = F X. By Proposition 2.3, E = X. Hence △ABC ∼ = △DEF . Proposition 18. If in △ABC we have ∠B ∼ = ∠C, then AB ∼ = AC and △ABC is isosceles. Proof. Consider the correspondence of vertices A ↔ A, B ↔ C, and C ↔ B. By C-1 BC ∼ = BC. By ∼ hypothesis ∠C ∼ ∠B, so by Proposition 3.17, △ABC △ACB. By the definition of congruent triangles = = AB ∼ = AC, so by the definition of isosceles triangle △ABC is isosceles. −−→ −−→ −−→ −−→ −−→ −−→ Proposition 19 (Angle Addition). Given BG between BA and BC, EH between ED and EF , ∠CBG ∼ = ∠F EH, and ∠GBA ∼ = ∠HED. Then ∠ABC ∼ = ∠DEF . Proof. By the crossbar theorem we may choose G so that A ∗ G ∗ C. By C-1 we may choose D, F , and H so that AB ∼ = △DEH. = ∠DEH, so by SAS △ABG ∼ = EH. By hypothesis ∠ABG ∼ = EF , and BG ∼ = DE, BC ∼ ∼ ∼ Similarly, by hypothesis ∠CBG = ∠F EH, so by SAS △CBG = △F EH. By the definition of congruent triangles AG ∼ = DH and GC ∼ = HF . We next need to show D, H, and F are collinear. By the definition of congruent triangles ∠AGB ∼ = ∠DHE and ∠CGB ∼ = ∠F HE. Since A, G, and C are collinear ∠AGB and ∠CGB are supplementary. By Proposition 5 ∠CGB is congruent to the supplement of ∠DHE. Denote this supplement by ∠EHX. By −−→ −−→ −−→ C-4 HX is unique, so HX = HF . Then ∠DHE is supplementary to ∠F HE, so F , H, and D are collinear. −−→ −−→ −−→ Since EH is between ED and EF , H is in the interior of ∠DEF , so D ∗ H ∗ F by Proposition 3.7. Since AG ∼ = △DEF , so by the definition of = DF . By SAS △ABC ∼ = HF , by C-3 AC ∼ = DH and GC ∼ ∼ congruent triangles ∠ABC = ∠DEF . −−→ −−→ −−→ −−→ −−→ −−→ Proposition 20 (Angle Subtraction). Given BG between BA and BC, EH between ED and EF , ∠CBG ∼ = ∠F EH, and ∠ABC ∼ = ∠DEF . Then ∠GBA ∼ = ∠HED. Proof. We proceed as in the proof of Proposition 3.11. Suppose ∠GBA ∼ 6 ∠HED (RAA). By C-4 there = −−→ ←→ −−→ is a unique ray EX on the same side of EH such that ∠GBA ∼ = ∠HEX. By the RAA hypothesis EX 6= −−→ ED. By hypothesis ∠F EH ∼ = ∠CBG, and by RAA hypothesis ∠XEH ∼ = ∠ABG, so by Proposition 10 ∼ ∼ ∠XEF . By the uniqueness part of ∠DEF , so by C-5 ∠DEF ∠XEF . By hypothesis ∠ABC ∠ABC ∼ = = = −−→ −−→ ∼ C-4 EX = ED, but this is a contradiction, so ∠GBA = ∠HED. MATH 4510/5510: Brown Congruence-4 −−→ −−→ −−→ −−→ Lemma 1. Given ∠ABC ∼ = ∠DEF , then for any ray BG between BA and BC, there is a unique ray EH −−→ −−→ between ED and EF such that ∠CBG ∼ = ∠F EH. A D G B H C E F Proof. By the Crossbar Theorem we can choose G so that A ∗ G ∗ C. By C-1 we can choose points D and F such that AB ∼ = DE and BC ∼ = EF . By SAS △ABC ∼ = △DEF , and by the definition of congruent triangles ∠BCA ∼ = ∠EF D and AC ∼ = DF . Then by Proposition 3.12 there is a unique point H on DF such that CG ∼ = F H. Again by SAS, △CBG ∼ = △F EH, so by the definition of congruent triangles ∠CBG ∼ = ∠F EH. −−→ −−→ −−→ We only need to show that EH is between ED and EF . Since H is on DF , H is between D and F , so by −−→ −−→ −−→ Proposition 3.7 EH is between ED and EF . −−→ −−→ −−→ ∼ ∠GEF . Definition. ∠ABC < ∠DEF means there exists a ray EG between ED and EF such that ∠ABC = Proposition 21 (Ordering of Angles). 1. Exactly one of the following conditions holds (trichotomy): ∠P < ∠Q, ∠P ∼ = ∠Q, or ∠P > ∠Q. 2. If ∠P < ∠Q and ∠Q ∼ = ∠R, then ∠P < ∠R. 3. If ∠P > ∠Q and ∠Q ∼ = ∠R, then ∠P > ∠R. 4. If ∠P < ∠Q and ∠Q < ∠R, then ∠P < ∠R. (transitivity). Proof. This proof is very similar to the proof of Proposition 3.13. For labeling purposes we say ∠P = ∠ABC, ∠Q = ∠DEF , and ∠R = ∠GHI. −−→ ←→ 1. Suppose ∠ABC ∼ 6 ∠DEF . By C-4 there exists a unique ray EX on the same side of EF as D such = −−→ −−→ −−→ −−→ −−→ −−→ −−→ that ∠ABC ∼ . EX either is between EF and ED or EX is not between EF and ED. If EX = ∠XEF −−→ −−→ is between EF and ED, then ∠ABC < ∠DEF . −−→ ←→ −−→ −−→ −−→ Suppose EX is not between EF and ED. Since X is on the same side of EF as D and EX is not −−→ −−→ ←→ between EF and ED, we know that X and F are on opposite sides of ED. By Lemma 2 and Corollary −−→ ←→ −−→ 1 every point except D on DF is on the opposite side of ED as every point of EX, so segment DF −−→ −−→ −−→ does not intersect EX. By a similar argument with the ray opposite EX and F D, we can show that ←→ ←→ segment DF does not meet EX. Hence D is on the same side of EX as F , so D is interior to ∠XEF . −−→ −−→ −−→ −−→ −−→ −−→ Then ED is between EX and EF . By Lemma 4 there exists a unique ray BY between BA and BC such that ∠DEF ∼ = ∠Y BC. Hence ∠ABC > ∠DEF . −−→ −−→ −−→ 2. Since ∠ABC < ∠DEF , there exists a ray EX between ED and EF such that ∠ABC ∼ = ∠XEF . −−→ −−→ −→ ∼ By Lemma 4 there is a unique ray HY between HG and HI such that ∠Y HI = ∠XEF . By C-5 ∠ABC ∼ = ∠Y HI, so ∠ABC < ∠GHI. −−→ −−→ −−→ 3. Since ∠ABC > ∠DEF , there exists a ray BX between BA and BC such that ∠XBC ∼ = ∠DEF . By C-5 ∠XBC ∼ = ∠GHI, so ∠ABC > ∠GHI. −−→ 4. Suppose ∠ABC < ∠DEF and ∠DEF < ∠GHI. Since ∠ABC < ∠DEF , there is a unique ray EX − −→ −−→ −−→ between ED and EF such that ∠ABC ∼ = ∠XEF . Since ∠DEF < ∠GHI, there is a unique ray HY −−→ −→ − − → − − → between HG and HI such that ∠DEF ∼ = ∠Y HI. By Lemma 4, there is a unique ray HZ between HY −→ −→ −−→ −−→ −→ −−→ −−→ and HI such that ∠XEF ∼ = ∠ZHI. By C-5 ∠ABC ∼ = ∠ZHI. Since HI ∗ HZ ∗ HY and HI ∗ HY ∗ HZ, −→ −−→ −−→ by Lemma 3 HI ∗ HZ ∗ HZ. Then by definition ∠ABC < ∠GHI. MATH 4510/5510: Brown Congruence-5 Proposition 22 (SSS). Given △ABC and △DEF . If AB ∼ = DE, BC ∼ = EF , and AC ∼ = DF , then △ABC ∼ = △DEF . ←→ Proof. By Corollary 4, since AC ∼ = DF we can pick a point G uniquely on the opposite side of AC as B such that △DEF ∼ = GC. Then by = AG and EF ∼ = △AGC. By the definition of congruent triangles DE ∼ ∼ ∼ ∼ C-2 AB = AG and BC = GC. We will show that △ABC = △AGC. Since B and G are on opposite sides of ←→ ←→ AC, segment BG intersects AC at X. By B-3, X ∗ A ∗ C, A = X, or A ∗ X ∗ C. The circumstances X = C and A ∗ C ∗ X are equivalent to X = A and X ∗ A ∗ C, respectively. Suppose X ∗ A ∗ C. Consider △CBG. Since BC ∼ = CG, △CBG, by Proposition 3.10 ∠CBG ∼ = ∠CGB. ∼ Now consider △ABG. Since AB = AG, by Proposition 3.10 ∠ABG ∼ = ∠AGB. Then by Proposition 3.20 (angle subtraction) ∠CBA ∼ = ∠CGA. By SAS △ABC ∼ = △AGC. Suppose A = X. Since CG ∼ = CB in △CBG, by Proposition 10 ∠B ∼ = ∠G. Then by SAS △ABC ∼ = △AGC. Suppose A ∗ X ∗ C. Consider △CBG. Since BC ∼ = CG, △CBG, by Proposition 3.10 ∠CBG ∼ = ∠CGB. ∼ Now consider △ABG. Since AB = AG, by Proposition 3.10 ∠ABG ∼ = ∠AGB. Then by Proposition 3.19 (angle addition) ∠CBA ∼ = ∠CGA. By SAS △ABC ∼ = △AGC. In all three cases △ABC ∼ = △AGC. By the definition of congruent triangles ∠B ∼ = ∠G. Since △DEF ∼ = ∼ ∼ ∼ △AGC, ∠E = ∠G. By C-5 ∠B = ∠E, so by SAS △ABC = △DEF . Proposition 23. All right angles are congruent to each other. Proof. Suppose ∠DAB ∼ 6 = ∠DAC and ∠HEF ∼ = ∠HEG are two pairs of right angles. Assume ∠DAB ∼ = ∠HEF (RAA). By Proposition 3.21 (a), either ∠DAB > ∠HEF or ∠DAB < ∠HEF . Without loss of −−→ −−→ −−→ generality suppose ∠DAB > ∠HEF . Then there is AX between AB and AD such that ∠XAB ∼ = ∠HEF . By Proposition 3.14 ∠XAC ∼ = ∠HEG. Since ∠DAC ∼ = ∠DAB by hypothesis, and ∠DAB > ∠HEF by by RAA hypothesis, we have ∠DAC > ∠HEF by Proposition 3.21 (c). Since ∠HEF ∼ = ∠HEG by hypothesis, we have again by Proposition 3.21 (c) ∠DAC > ∠HEG. From above since ∠XAC ∼ = ∠HEG we have ∠DAC > ∠XAC by Proposition 3.21 −−→ −−→ −−→ −−→ −−→ −→ (c). By Proposition 3.8 (c), since AX is between AB and AD, we know that AD is between AX and AC, −→ −−→ since AC is the ray opposite to AB. Then ∠DAC < ∠XAB, but this contradicts Proposition 3.21 (a). Hence ∠DAB ∼ = ∠HEF .